2015
DOI: 10.5812/asjsm.23806
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Therapeutic Sequence of Hot Pack and Ultrasound on Physiological Response Over Trigger Point of Upper Trapezius

Abstract: Background:Musculoskeletal pain is a common problem among athletes. Apart from sport injuries, the myofascial pain syndrome is another important problem that affects performance of the athlete.Objectives:The aim of this study was to evaluate the effects of therapeutic sequences of the hot pack in combination with ultrasound on the physiological responses over the latent myofascial trigger point (LMTrP) of upper trapezius muscle.Materials and Methods:Thirty subjects with a latent myofascial trigger point (LMTrP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…19 Additionally, Rickards came to the conclusion that TENS, a quickfix painkiller, and laser, a short-term remedy, could both help myofascial trigger patients. 20 Previous randomized trials assessed the immediate effects of hot packs combined with ultrasonography 21 and revealed that the TrPs significantly improved when TENS was used in conjunction with heated packs, myofascial release, and active ROM exercises. 22 Exercise has also been shown to reduce the severity of myofascial pain in individuals, and it seems that combining stretching and strengthening activities has the greatest benefit.…”
Section: Discussionmentioning
confidence: 99%
“…19 Additionally, Rickards came to the conclusion that TENS, a quickfix painkiller, and laser, a short-term remedy, could both help myofascial trigger patients. 20 Previous randomized trials assessed the immediate effects of hot packs combined with ultrasonography 21 and revealed that the TrPs significantly improved when TENS was used in conjunction with heated packs, myofascial release, and active ROM exercises. 22 Exercise has also been shown to reduce the severity of myofascial pain in individuals, and it seems that combining stretching and strengthening activities has the greatest benefit.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 Thermal therapies are physiologically known to increase tissue metabolism, collagen elasticity, capillary blood flow, and reduce muscle spasm. 47,48…”
Section: Discussionmentioning
confidence: 99%
“…The routine Physiotherapy consisted of pulsed Short Wave Diathermy (SWD) with frequency 27.12 MHZ [ 16 ], Ultrasonic Therapy (US) with frequency 1.0 MHZ and intensity 1.45w/cm 2 [ 17 ] and Transcutaneous Electrical Nerve Stimulator (TENS) 2–200 HZ with output current < 20 Ma width 200 μ seconds along with continuous mode. Exercises were comprised of shoulder strengthing and stretching exercises that were performed for 5 s with 10 repetitions for both experimental and care groups as shown in Table 1 [ 18 ].…”
Section: Methodsmentioning
confidence: 99%